Enhancing the Fuel Efficiency and Environmental Performance of Spark-Ignition Engines through Advancements in the Combined Power Regulation Method - Jonas Matijošius; Sergiy Rychok; Yurii Gutarevych; Yevhenii Shuba; Oleksander Syrota; Alfredas Rimkus; Dmitrij Trifonov (Energies, 2024)
A major issue with spark-ignition engines is their fuel inefficiency and negative environmental effects, especially in urban driving situations. This topic is of utmost importance considering the increasing apprehension over environmental contamination and the need for enhanced energy efficiency. The research’s originality resides in its strategy to tackling this issue without necessitating intricate engine changes, a manner not commonly used. The research uses a dual strategy that integrates both theoretical and experimental approaches. The theoretical component entails developing models to forecast the effects of different cylinder deactivation strategies on fuel consumption and emissions. Important factors to address in this theoretical model are the introduction of air into cylinders that are not in use and the stopping of fuel supply. The experimental component involves conducting bench experiments on a modified spark-ignition engine to verify the theoretical conclusions. These tests assess performance metrics, such as fuel economy and environmental effect, under different load situations. The study’s findings are encouraging. The study reveals that disabling a specific group of cylinders while permitting unrestricted air intake might result in significant improvements in fuel economy, anywhere from 1.5% to 10.5%, depending on the engine’s workload. Bench testing revealed a maximum improvement of 10.8%, which demonstrates the efficacy of this strategy. The study’s findings indicate that the use of the integrated power regulation approach greatly improves fuel efficiency and decreases the impact of the environmental consequences of spark-ignition engines, especially in situations of low load and idling. This technology demonstrates its feasibility as a solution that can be seamlessly incorporated into current engine designs with few adjustments, providing a practical and environmentally responsible option for enhancing vehicle performance. The results indicate that this approach has wide-ranging potential uses in the automotive sector, particularly for urban cars that often function in situations with modest levels of demand. By using this approach, manufacturers may attain enhanced fuel efficiency and diminish emissions, this contributing to the development of more sustainable urban transportation options.